Computational Fluid Dynamics Simulation of Temperature Distribution and Flow Characterization in a New Loop Heat Pipe Model - Restiawan, Muhammad Mika Ramadhani; Kusuma, Mukhsinun Hadi; Rozi, Khoiri; Kiono, Berkah Fajar Tamtomo; Yunus, Muhammad; Wirza, Alif Rahman; Pambudi, Yoyok Dwi Setyo; Butarbutar, Sofia Loren; Giarno; Hatmoko, Sumantri (Jurnal Teknologi Reaktor Nuklir Tri Dasa Mega, 2026)
The loop heat pipe (LHP) is being considered for passive cooling systems in nuclear installations. A combined approach of simulation and experimentation is essential to achieve comprehensive knowledge of LHP performance. Research on LHP using Computational Fluid Dynamics (CFD) is necessary to understand phenomena that are difficult to observe experimentally. This study examines the temperature distribution and flow characteristics in a new LHP model. The method used in this research is numerical simulation using CFD with ANSYS FLUENT software. In the simulation, the LHP has an inner diameter of 0.1016 m. The LHP features a wick made from a bundle of capillary pipes without a compensation chamber. Demineralized water is used as the working fluid with a filling ratio of 100% of the evaporator volume. The hot water temperature in the evaporator section is set at 70 °C, 80 °C, and 90 °C. The temperature on the outer surface of the condenser pipe is determined using experimental temperature inputs. An inclination angle of 5° and an initial pressure of 12,100 Pa are applied to the LHP. The CFD simulation results show that the temperature distribution profile under steady-state conditions in the loop heat pipe is relatively uniform. The temperature difference between the evaporator and condenser remains consistent. The working fluid flow in the LHP is driven by buoyancy forces, allowing the fluid to circulate in two phases from the evaporator to the condenser, while the condensate returns from the condenser to the evaporator. In conclusion, the temperature distribution and flow patterns in the LHP are consistent with common phenomena observed in heat pipes. This modeling approach can be used to determine the temperature distribution and flow profiles in LHP systems with similar dimensions under various thermal conditions.